Revision of the south Asian amisegine genus Cladobethylus Kieffer, 1922 (Hymenoptera, Chrysididae, Amiseginae) - Lynn S. Kimsey (Journal of Hymenoptera Research, 2019)
The south Asian genus Cladobethylus Kieffer, 1922, is reviewed, with a key to the species. Five new species are described, one from the island of Borneo (Cl. darlingi), two from Thailand (Cl. densepunctatus and Cl. thailandicus), one from Korea (Cl. koreensis), and one from Sumatra (acehensis).